Effects of plyometric training performed on different surfaces and with different types of footwear on the neuromuscular performance of team-sport athletes: A systematic review - Sanchez-Ottado, G. R.; Spyrou, K.; Pereira, L. A.; Alcaraz, P. E.; Zabaloy, S.; Loturco, I.; Freitas, T. T. (Biology of Sport, 2025)
This systematic review aimed to analyze the effects of plyometric training (PT) performed on different surfaces and with different types of footwear on the neuromuscular performance of team-sport athletes, and to properly delineate the role of these specific factors (i.e., surface type and footwear) on PT outcomes. A systematic search was conducted according to the preferred reporting items for systematic reviews and meta analyses guidelines using PubMed, Scopus, and Web of Science for articles published before May 2024. From the total of 2832 articles, 35 met the inclusion criteria for the systematic review. The results indicate that sand surfaces seem to be more effective than other surfaces in increasing neuromuscular performance. Specifically, studies that investigated the intervention process found significant improvements in performance metrics after plyometric sand training. In terms of acute effects, the results were diverse and inconclusive, with no clear pattern of evidence. Despite presenting lower improvements overall, rigid surfaces required a lower number of contacts compared to other types of surfaces to achieve similar performance gains. PT in water is also recommended to promote neuromuscular adaptations. Regarding footwear, minimalist and rigid options were found to lead to higher improvements in various neuromuscular performance variables, likely due to enhanced energy efficiency and stability during PT sessions. The included studies indicated that PT on sand is highly effective for improving neuromuscular adaptations. However, training on rigid surfaces is more time-efficient, while aquatic surfaces are also recommended. Additionally, minimalist or rigid footwear acutely improves various athletic performance variables. Overall, when designing a PT program, it is crucial to consider both the surface and footwear to maximize neuromuscular adaptations.